Complex numbers and their application to representing curves and domains on the complex plane - Dimitrova, S. D.; Girya, N. P.; Burlayenko, V. M.; Naboka, O. O. (National Technical University "Kharkiv Polytechnic Institute", 2024)
The educational-methodological textbook focuses on an important topic in mathematical analysis – the calculus of complex functions with a single variable. This textbook extensively explores the fundamental theoretical concepts and offers solutions to standard problems. It incorporates exercises for study and a series of tasks for individual student work. Tailored for students and lecturers in higher technical educational institutions.

Навчально-методичний посібник присвячений важливій темі математичного аналізу – обчисленню функцій комплексної змінної. В ньому детально розглядаються фундаментальні теоретичні концепції та надаються розв'язки стандартних задач. Посібник також включає вправи для вивчення та серію завдань для індивідуальної роботи студентів. Розраховано на студентів і викладачів вищих технічних навчальних закладів.
Комплексні числа та їх застосування для представлення кривих і областей на комплексній площині
Keywords: еducational-methodological textbook; individual work; complex numbers; complex plane; representing curves; навчально-методичний посібник; самостійна робота; комплексні числа; представлення кривих